1981
DOI: 10.1136/pgmj.57.666.210
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine therapy in acromegaly. A long-term review of 35 cases

Abstract: SummaryBromocriptine Parlodel, Sandoz)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…The doses of bromocriptine used to treat chronic hepatic encephalopathy are modest compared with those used in Parkinsonism (Calne et al, 1978;Parkes, 1979), acromegaly (Sachdev et al, 1981) and in the treatment of prolactinomas (Archer et al, 1982). Despite the fact that many patients have been exposed to much higher doses of bromocriptine for as long or longer than the patients reported here, no previous reports of bromocriptine-associated ototoxicity exist.…”
Section: Discussioncontrasting
confidence: 39%
“…The doses of bromocriptine used to treat chronic hepatic encephalopathy are modest compared with those used in Parkinsonism (Calne et al, 1978;Parkes, 1979), acromegaly (Sachdev et al, 1981) and in the treatment of prolactinomas (Archer et al, 1982). Despite the fact that many patients have been exposed to much higher doses of bromocriptine for as long or longer than the patients reported here, no previous reports of bromocriptine-associated ototoxicity exist.…”
Section: Discussioncontrasting
confidence: 39%
“…However, subsequent studies reported relatively low rates of GH response with only 20-40% of patients achieving GH levels <5 μg/l, and only 10-20% achieving normalization of IGF-1 levels, despite subjective clinical improvement in 50% of patients [65,70,71].…”
Section: Secondary Treatmentmentioning
confidence: 91%
“…Some concerns persist that the rise in GH which occurs with pegvisomant therapy may have some deleterious effects on tumor growth [80], however, the rapidly growing body of clinical experience is reassuring; Schreiber et al has recently published the clinical outcomes for 229 patients treated for a mean of 51.8 weeks, with tumor growth verified in only 3.1% of patients [81]. Safety concerns aside, the cost of pegvisomant remains the primary barrier to its widespread use, which was the same issue with bromocriptine 25 years ago [70]. Currently, pegvisomant offers a highly effective, last-line medical treatment for patients who have failed lower-cost options.…”
Section: Clinical Trialsmentioning
confidence: 93%
“…34,35 These agents are orally active and less expensive compared with other medical therapies. The efficacy of bromocriptine in controlling acromegaly, however, is disappointing.…”
Section: Efficacy Of Dopamine Agonistsmentioning
confidence: 99%